Investigation of Heavy Metals in Ground Water in And Around Mahadevapura,Bengaluru - Prashanth N,Dr.Y. Ramalinga Reddy (International Journal of Advanced Science and Technology, 2020)
The present work has carried out to investigate the heavy metal content in the ground water of the area Mahadevapura, Bangalore. Where the location has been divided into 4 zones, industrial, commercial, residential and agricultural from where the ground water is been collected and analysed by using Atomic adsorption spectrophotometer (AAS). Total 20 samples were collected and analysed for water quality parameters (pH, EC, Carbonates, Bicarbonates, chlorides, sulphates, calcium, magnesium, sodium, potassium) and heavy metals(Lead, Iron, Nickel and Copper). The result shows that some samples are exceeding with bicarbonates, chlorides, Magnesium, sodium in water quality analysis and in heavy metals Iron and Nickel are more than permissible limits